2017
DOI: 10.3390/ijerph14010037
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Indoor Air Quality in Houses of Macedonia

Abstract: People who live in buildings are exposed to harmful effects of indoor air pollution for many years. Therefore, our research is aimed to investigate the indoor air quality in family houses. The measurements of indoor air temperature, relative humidity, total volatile organic compounds (TVOC), particulate matters (PM) and sound pressure level were carried out in 25 houses in several cities of the Republic of Macedonia. Mean values of indoor air temperature and relative humidity ranged from 18.9 °C to 25.6 °C and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…Another possible explanation for these levels of PM could be regional biomass burning that occurs during winter and spring [25]. Results obtained in previous studies found that PM in homes increased during cold seasons, when heating is common and ventilation is reduced, because doors and windows are typically closed, thus trapping PM inside [26,27].…”
Section: Seasonal Variation Of Indoor Air Quality and Indoor And Outdmentioning
confidence: 97%
“…Another possible explanation for these levels of PM could be regional biomass burning that occurs during winter and spring [25]. Results obtained in previous studies found that PM in homes increased during cold seasons, when heating is common and ventilation is reduced, because doors and windows are typically closed, thus trapping PM inside [26,27].…”
Section: Seasonal Variation Of Indoor Air Quality and Indoor And Outdmentioning
confidence: 97%
“…In Macedonia, the recommended value for human exposure to TVOCs was exceeded in 32% of houses; and mean concentrations of PM 2.5 from 16.80 µg/m 3 to 30.70 µg/m 3 were established [33].…”
Section: Introductionmentioning
confidence: 99%
“…Measurements were made in 25 homes specifically in the town of Prilep, located in the southwestern part of Macedonia. Characteristics such as: type of building (single-family houses and apartments in multi-family buildings); age of building (construction finished in years from 1960 to 2005); renovation (years of 2000 -2013); smoking; and heating system (central system -pellets, wood; electric energy; wood stove; heat pump) are presented in study [12].…”
Section: Monitored Homesmentioning
confidence: 99%